Waqf management and administration in Malaysia: its implementation from the perspective of Islamic law / Mohd Afendi Mat Rani and Asmah Abdul Aziz - Mat Rani, Mohd Afendi; Abdul Aziz, Asmah (Universiti Teknologi MARA Cawangan Selangor, 2010)
Endowment is one of the Islamic institutions that has existed since the time of Prophet Muhammad SAW. It serves as a catalyst for economic growth and development of the Muslims. Endowment is not only a ritual matter to Allah SWT but is also considered as an economic institution which benefits the Muslims. The management and administration of the waqf property is an important issue to be resolved in Malaysia. This article includes the discussion of the powers of a trustee of an endowment property in Malaysia. A number of legal obstacles and constraints that impeded efforts to develop waqf property in Malaysia are identified. Thus, the implementation of a waqf management must be aligned with the waqf legislation so that there is a continuity of the reward to the waqf donor through good governance and systematic procedures. The trustee who manages the waqf property is responsible to look after, preserve and develop the land that is donated in order to collect income which can be distributed to the recipient. Although the Religious Council is appointed as the sole trustee on the management of waqf in Malaysia, nevertheless, from the practical aspect, these assets are still subjected to various acts made by Parliament.